Evaluación del impacto de la ceniza volcánica emitida por el volcán Tungurahua, sobre los suelos destinados a la explotación agrícola. ( Cantón Quero). - Jacome Mogro, Emerson Javier (2011)
The research was carried out; in the canton Quero County of Tungurahua with latitude of 1°27" South, longitude of 78°37" West, to 3200 m. above sea level The objectives were: GENERAL: To evaluate the impact of the fall of volcanic ash. SPECIFIC OBJECTIVES: To carry out the evaluation from the environmental impact; To determine the foliate affections in crops; To determine the impact in characteristic the floor; To determine the social effect in the inhabitants. The environmental impact was determined with LEOPOLD, the damage to foliate in crops with the application of a totally random design, effects in the floor with soil analyze , and to value the effects in the inhabitants of the canton Quero. From the obtained results was conclude that: The impact of the fall of ash is negative in 76.74% , for what all economic activity should be controlled. In the crops that have damages on the foliate area with 80% in corn, in onion and oat with values of 3.20 and 1.60% respectively, with alimentary reduction of 85.71%. In the chemical characteristics of the floor, it has that the value of: pH in the affected floors went from 3.3 to 5.0, The organic matter in the ash of it was 0.10% and nutrients values low and insufficient for vegetable develop. The 99% of the population´s is affected by the fall of volcanic ash, manifested total or partial loss of its cultivations, the sanity, the fertility of the floors has lowered. Of all that studied was recommending that: It should be given to know all type of information through specialists in Administration of the volcanic risk. To cultivate tolerant plants to the fall of ash as (Allium sp.) and (Hordeum sp.). To carry out an appropriate plan from the territorial use, incorporating the volcanic risk. To improve the characteristics of the cultivation floors affected by the fall of ash it should be carried out whitewashed to correct pH, incorporating organic matter; carrying out whitewashed. All this according to the necessities from each farmer and depending from the intensity of ash has fallen. To coordinate the help in organized form, with an emergency plan according to social and cultural c ostumers of the population.